Sinergi Kantor Pelayanan Pajak dan Pemerintah Daerah dalam Rangka Peningkatan Kepatuhan Perpajakan Wajib Pajak Kepala Urusan Keuangan Desa: Studi Kasus KPP Pratama Bengkulu Dua - Andre Nugroho; Desta Dwi Ramadhan; Fany Noor Fadilla; Muhammad Anugerah Ramadhan; veronicaulyarthasitumorang (Jurnal Ragam Pengabdian, 2026)
This study analyzes the synergy between the Tax Service Office (KPP) and local governments in improving tax compliance among Village Financial Affairs Officers, who act as withholding agents for village expenditures. Despite a structured and predictable village budgeting system, tax noncompliance persists, contributing to the tax gap through inaccurate withholding, delayed remittance, and incomplete reporting. Using a qualitative approach—literature review, documentation, and semi- structured interviews—this research identifies limited competence, low fiscal literacy, and weak administrative capacity as key causes of noncompliance. The study finds that coordinated reconciliation programs, data sharing, and MoUs between KPP and local governments significantly improve tax accuracy. Evidence from Regency X shows increased tax payments and higher revenue-sharing allocations following reconciliation. The research recommends strengthening coordination, expanding MoU implementation, enhancing tax education for village officers, and introducing mandatory tax training or certification for future Village Financial Affairs Officers.